2015
DOI: 10.1111/jeu.12213
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lipids and Proteins Associated to the Cell Wall of the Acapsular Mutant Cryptococcus neoformans Cap 67

Abstract: Cryptococcus neoformans is an opportunistic human pathogen that causes life-threatening meningitis. In this fungus, the cell wall is exceptionally not the outermost structure due to the presence of a surrounding polysaccharide capsule, which has been highly studied. Considering that there is little information about C. neoformans cell wall composition, we aimed at describing proteins and lipids extractable from this organelle, using as model the acapsular mutant C. neoformans cap 67. Purified cell wall prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
(139 reference statements)
1
7
0
Order By: Relevance
“…In Cryptococcus, PC species, namely, 34 Cryptococcus contain very long chain hydroxylated fatty acyls (24C or 26C). These results are consistent with a previous study on cap67 (an acapsular mutant of Cryptococcus neoformans), which showed similar phosphoglyceride composition (47). Nonetheless, a more targeted study is required to confirm the nonexistence of phosphoglyceride species with hydroxylated fatty acyls.…”
Section: Downloaded Fromsupporting
confidence: 91%
See 3 more Smart Citations
“…In Cryptococcus, PC species, namely, 34 Cryptococcus contain very long chain hydroxylated fatty acyls (24C or 26C). These results are consistent with a previous study on cap67 (an acapsular mutant of Cryptococcus neoformans), which showed similar phosphoglyceride composition (47). Nonetheless, a more targeted study is required to confirm the nonexistence of phosphoglyceride species with hydroxylated fatty acyls.…”
Section: Downloaded Fromsupporting
confidence: 91%
“…This is primarily because the structure and biosynthesis of several fungal lipids is different from mammalian lipids (10). In Cryptococcus, several studies have shown the role of lipids in its growth and virulence, but not many studies have been done to characterize their compositions or the genetic makeup of the biosynthetic pathways (19,20,47,60). In this study, we have determined the compositions of the most common lipids of Cryptococcus, Supplemental Material can be found at: using various spectroscopic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 16 specific immunogenic proteins of P. lutzii can be divided into three main groups. Group 1 comprises seven proteins that have been widely reported in Paracoccidioides under experimental physiological conditions according to STRING analysis, namely, triosephosphate isomerase, glyceraldehyde-3-phosphate dehydrogenase, citrate synthase, isocitrate lyase, enolase, HSP60-like protein, and an uncharacterized protein (thioredoxin-like superfamily) [ 54 , 70 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Proteins included in group 2 are antigens that already have been described in human PCM, such as triosephosphate isomerase, glyceraldehyde-3-phosphate dehydrogenase, fructose-bisphosphate aldolase [ 70 ], or Paracoccidioides antigens that already have been related to eliciting a humoral immune response in BALB/c mice, such as transketolase, HSP60-like protein, and isocitrate lyase (all shared with PS3) [ 71 ].…”
Section: Discussionmentioning
confidence: 99%